KECERDASAN SPASIAL DALAM MEMAHAMI TRIMATRA: STUDI STRATEGI PEMBELAJARAN MATA KULIAH NIRMANA 2 (TRIMATRA) - Ernawati Ernawati (Universitas Pendidikan Ganesha, 2020)
ABSTRAK Tujuan penelitian ini untuk berdiskusi strategi pembelajaran yang oftimal sehingga tercapai tujuan sesuai dengan visi dan misi mata kuliah Nirmana 2 (Trimatra) yang tercantum pada kurikulum. Metode pada penelitian ini menerapkan metode tindakan kelas (PTK) dengan pendekatan model PTK dari Kurt Lewin. Nirmana 2 (Trimatra) mempersiapkan mahasiswa untuk memiliki kepekaan rasa, ketajaman analisis visual dan pemahaman mendalam terhadap ilmu dasar seni rupa dan desain. Nirmana berpengaruh terhadap mata kuliah lainnya yang berhubungan denagn teori maupun praktik desain komunikasi visual. Modifikasi strategi pembelajaran nirmana 2 (Trimatra) dengan kontekstual (visual-spasial) dan evaluasi penilaian mampu menjadi poin penting dalam mengatur suasana kelas yang kondusif, meningkatkan kualitas semangat belajar dan menigkatkan pemahaman serta kreativitas mahasiswa untuk berkarya.Katakunci : Nirmana 2, Spasial, Strategi Pembelajaran, visualABSTRACT The purpose of this study is to discuss optimal learning strategies so that the objective is achieved under the vision and mission of Nirmana II (Trimatra) courses listed in the curriculum. The method in this study applied classroom action research (PTK) with the research approach from Kurt Lewin, which aimed to explore the strategic roles of the spatial intelligence learning toward the process of students’ creativity development in Nirmala learning. Arts and design students have a close relationship with creativity and sensitivity in which they need preparation in understanding the governance of design elements. Spatial intelligence is an ability to visualize the ideas relating to space and place. Spatial intelligence is an intelligence possessed by most fine art and design students. Nirmana II (Trimatra) prepares students to have a sense of taste, sharpness of visual analysis, and a deep understanding of the basic fine arts and design. Nirmana influences other courses relating to the theory and practice of visual communication design. Modification of the Nirmana II learning strategy (Trimatra) with contextual (visual-spatial) and evaluation assessment can be important points in managing a conducive classroom atmosphere, improving the quality of enthusiasm for learning, and increasing students' understanding and creativity to work. The analysis process is done by collecting data that is measurable.Keywords: Nirmana II, spatial, learning strategies, visual